Catalytic pyrolysis of waste plastic into liquid fuel - Slavčo Aleksovski; Gaceva Gordana Bogoeva (Zaštita Materijala)
Process of pyrolysis is a thermochemical process conducted at high temperatures and usually in presence of catalysts. Different type of catalysts, natural and synthetic, can be used for conversion of organic wastes into valuable fuels. The aim of this work is conversion of waste polyolefin mixture and production of liquid fuel using mixture of Al2O3 and SiO2 as a catalyst. Waste mixture was pyrolyzed at temperature range 400-550oC and obtained products were liquid fuel, gas and minor solid residue. Under the optimized reaction conditions, the condensed liquid fraction is much larger than the gaseous fraction. Different amounts of catalyst and polyolefin mixture as a feedstock were used. According to the obtained results, the retention time and the percent of SiO2 in the catalyst mixture have predominant effect on the amount of liquid product. Decreasing the quantity of SiO2 in the catalyst mixture increased the yield of liquid product. The physical properties of obtained liquid products were characterized and according to the measured values, liquid fuel belongs to light fraction of diesel fuel.